PENDIDIKAN DASAR 9 TAHUN PADA MASYARAKAT SUKU DAYAK BAKUMPAI DI KELURAHAN PENDANG KECAMATAN DUSUN UTARA - Piagusleani D Munthe (JURNAL SOCIUS, 2016)
This research aimed to explaine and to describe the life of basic educations 9th of students at Suku Dayak Bakumpai in Kelurahan Pendang Kecamatan Dusun Utara. This research used the describe method. Interview, observation, and documentation are used in collecting the data. The result of this research show the cause of students drop out of school, they are economic problems, the location of Pendang is far away from the city, and the enviromnent factor.Kata Kunci : pendidikan dasar 9 tahun pada masyarakat Suku Dayak Bakumpai